Finding home: (re)discovering female identity in Barbara Kingsolver`s Prodigal summer - Novaes, Lúcia Cavalcanti (Kansas State University, 2013)
This thesis analyzes the protagonists’ pursuit of alternatives to traditionally patriarchal value through economic and ecofeminist critical lenses. The female protagonists in Prodigal Summer resist being identified through the social legacy of coverture that is still present in the small Appalachian town they live. Lusa, Deanna, and Nannie demonstrate that their socio-economic independence, acquired mainly due to their educational background, allows them not only to disconnect themselves from societal beliefs that the woman should be in the margins of the male presence, but also to interact with nature differently from others. The women’s separation from the institution of marriage and their embrace of motherhood as a matriarchal structure that mirrors the example of the coyotes’ families are studied as main examples of how they distance themselves from the other characters’ attitudes in the novel. This rejection of old ideologies of womanhood in terms of patriarchal structures and their fight for new spaces in society is also present in their struggle to physically inhabit spaces long considered male domains. Defeating the notion that women belong to the domestic space of the house, the protagonists pursue a feminist identity in much wider settings, including forests and farms. The characters’ choice to consider nature as their home demonstrates that they welcome the concept of ecology and recognize the interconnectedness present in nature. This study shows that because of the protagonists’ feminist views, they can imagine different ways to both manage the land and their families. The land ethics they acquire thus refers to humans and non-humans equally.
Keywords: Ecofeminism; Land; Feminism; Identity; Prodigal summer; Barbara Kingsolver; Literature (0401)